Who chooses my diet? The automated notification of people in the digital environment - Vidal-Sepúlveda, Martha; Olivares-Rodríguez, Cristian (Facultad de Filosofía y Letras, Universidad de Buenos Aires, 2021)
From the theoretical point of view, this work analyzes how technology configures the new digital environment, as a space of information flow that gives meaning to our relationship with the world and; the development of our digital identity as subjects in development that mean in the digital experience. In this context, search engines, as cultural software, offer a personalized information diet, providing answers to queries by means of biased results, elaborated from the behavior patterns of the subjects, demystifying the global access to information.